Answer:
p(4)=3
Step-by-step explanation:
p(4)=3(4)-9=12-9=3
Answer:
21
Step-by-step explanation:
Step 1:
0.6x - 0.1 = 0.5x + 2 Equation
Step 2:
0.1x - 0.1 = 2 Subtract 0.5x on both sides
Step 3:
0.1x = 2.1 Add 0.1 on both sides
Step 4:
x = 2.1 ÷ 0.1 Divide
Ansewr:
x = 21
Hope This Helps :)
Answer:
Pierre is right
Step-by-step explanation:
The correct formula for Exponential growth rate is given as:
y = a( 1 + r) ^t
Where
y = Amount after time t
a = Initial amount
r = Growth rate
t = time
From the question
a = 300
r = 2% = 0.02
Hence, our exponential growth rate =
y = 300( 1 + 0.02)^t
y = 300( 1.02)^t
Therefore, Pierre is right
Answer:
a) P(X=2)= 0.29
b) P(X<2)= 0.59
c) P(X≤2)= 0.88
d) P(X>2)= 0.12
e) P(X=1 or X=4)= 0.24
f) P(1≤X≤4)= 0.59
Step-by-step explanation:
a) P(X=2)= 1 - P(X=0) - P(X=1) - P(X=3) - P(X=4)= 1-0.41-0.18-0.06-0.06= 0.29
b) P(X<2)= P(X=0) + P(X=1)= 0.41 + 0.18 = 0.59
c) P(X≤2)= P(X=0) + P(X=1) + P(X=2)=0.41+0.18+0.29= 0.88
d) P(X>2)=P(X=3) + P(X=4)=0.06+0.06= 0.12
e) P(X=1 or X=4)=P(X=1 ∪ X=4) = P(X=1) + P(X=4)=0.18+0.06= 0.24
f) P(1≤X≤4)=P(X=1) + P(X=2) + P(X=3) + P(X=4)=0.18+0.29+0.06+0.06= 0.59